2017
DOI: 10.1080/16549716.2017.1267961
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the worldwide Millennium Development Goals campaign on maternal and under-five child mortality reduction: ‘Where did the worldwide campaign work most effectively?’

Abstract: Background: As the Millennium Development Goals campaign (MDGs) came to a close, clear evidence was needed on the contribution of the worldwide MDG campaign. Objective: We seek to determine the degree of difference in the reduction rate between the pre-MDG and MDG campaign periods and its statistical significance by region. Design: Unlike the prevailing studies that measured progress in 1990–2010, this study explores by percentage how much MDG progress has been achieved during the MDG campaign period and quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 32 publications
3
29
0
4
Order By: Relevance
“…The indicator with the most significant improvement on average was cellular access, and the indicator with the smallest improvement was the school enrollment rate. We found promising aggregate results in the Sub-Sahara African, South Asian, and East Asian & Pacific regions, consistent with the results of previous studies focusing on the impacts of the MDGs in low-income countries (Cha 2017;Cuenca-García et al 2019). The infant mortality rate, GDP per capita, cellular device access, and school enrollment showed significant improvements among all regions on average, while the indicators for women in parliament, maternal and infant mortality, and HIV rates varied greatly across regions.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The indicator with the most significant improvement on average was cellular access, and the indicator with the smallest improvement was the school enrollment rate. We found promising aggregate results in the Sub-Sahara African, South Asian, and East Asian & Pacific regions, consistent with the results of previous studies focusing on the impacts of the MDGs in low-income countries (Cha 2017;Cuenca-García et al 2019). The infant mortality rate, GDP per capita, cellular device access, and school enrollment showed significant improvements among all regions on average, while the indicators for women in parliament, maternal and infant mortality, and HIV rates varied greatly across regions.…”
Section: Discussionsupporting
confidence: 89%
“…The infant mortality rate, GDP per capita, cellular device access, and school enrollment showed significant improvements among all regions on average, while the indicators for women in parliament, maternal and infant mortality, and HIV rates varied greatly across regions. Despite improvement, the variability in the indicator improvement across regions and income groups addressed in this study reemphasizes the previous research findings (Cha 2017;Reddy and Sen 2013;McClure et al 2018). By assessing the average results across four different income groups, we found that the lower and lower-middle income groups had the most significant improvements.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…As a part of overall human development process, countries in sub-Saharan Africa have been striving to reduce the high maternal and child mortality rates. Driven by the Millennium Development Goals (MDGs), many countries in the region have been able to make concrete improvements in this regard [1,2]. Nonetheless, the sub-Saharan African countries continue to account for a staggering 66% of all pregnancy and childbirth related deaths in the world [3].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there may be a growing effort to explore additional factors which may also attribute to poor health among children's groups. Recent studies suggest that there are currently worldwide efforts in place to develop effective health related goals to try and reduce children's disease and mortality rates (Cha, 2017). To support such initiatives, current policies should address potential factors which may be associated with disease and negative health related out comes among children worldwide.…”
Section: Introductionmentioning
confidence: 99%